1999
DOI: 10.1021/jm990224w
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimeric Tacrine-Based Acetylcholinesterase Inhibitors:  Investigating Ligand−Peripheral Site Interactions

Abstract: Dimeric acetylcholinesterase (AChE) inhibitors containing a single 9-amino-1,2,3,4-tetrahydroacridine (tacrine) unit were constructed in an effort to further delineate structural requirements for optimal binding to the AChE peripheral site. Basic amines of differing hydrophobicity were selected as peripheral site ligands, and in each case, improvements in inhibitory potency and selectivity were seen relative to tacrine itself. AChE IC(50) values of the optimum dimers decrease significantly as the peripheral si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 20 publications
(69 reference statements)
3
92
0
Order By: Relevance
“…The organic layer was dried over Na 2 SO 4 and concentrated under reduced pressure to afford the crude product, which was purified by flash column chromatography, CH 2 Cl 2 /MeOH/aqueous 30 % NH 3 (7:3:0.1 v/v), to afford products 9 a-f. Analytical data of the tacrine linkers 9 a-f are in good agreement with previously described data. [33] General procedure for the synthesis of TFAHs 10 a-n: A solution of the corresponding N 1 -(1,2,3,4-tetrahydroacridin-9-yl)alkane-1,ndiamine 9 a-e or N 1 -(7-methoxy-1,2,3,4-tetrahydroacridin-9-yl)alkane-1,8-diamine 9 f (1.0 mmol) and paraformaldehyde (1.0 mmol) in MeOH/CH 2 Cl 2 (7 mL, 3:1 v/v) was stirred for 1 h at room temperature. Ferulic acid (1.0 mmol) and the corresponding isocyanide (1.0 mmol) were then added, and the reaction was stirred for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic layer was dried over Na 2 SO 4 and concentrated under reduced pressure to afford the crude product, which was purified by flash column chromatography, CH 2 Cl 2 /MeOH/aqueous 30 % NH 3 (7:3:0.1 v/v), to afford products 9 a-f. Analytical data of the tacrine linkers 9 a-f are in good agreement with previously described data. [33] General procedure for the synthesis of TFAHs 10 a-n: A solution of the corresponding N 1 -(1,2,3,4-tetrahydroacridin-9-yl)alkane-1,ndiamine 9 a-e or N 1 -(7-methoxy-1,2,3,4-tetrahydroacridin-9-yl)alkane-1,8-diamine 9 f (1.0 mmol) and paraformaldehyde (1.0 mmol) in MeOH/CH 2 Cl 2 (7 mL, 3:1 v/v) was stirred for 1 h at room temperature. Ferulic acid (1.0 mmol) and the corresponding isocyanide (1.0 mmol) were then added, and the reaction was stirred for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…9-Chlorotacrines 8 a,b were synthesized by following known procedures. [33][34][35] The latter chloro compounds were then treated with the appropriate alkylenediamines in 1-pentanol at reflux to obtain diamines 9 a-f. These diamines were then treated, by one-pot U-4CR, with formaldehyde, ferulic acid, and selected commercial isocyanides, in methanol/ dichloromethane (3:1 v/v) at room temperature for 24 h to obtain the expected TFAHs 10 a-n in 16-48 % overall yields (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…1) It is assumed that the primary role of the tether in a divalent drug is to reduce the loss of entropy that would occur upon binding two independent monomeric units. 1) The relationship between biological potency and the linker length has been discussed for bis-quaternary ammonium 2) and tacrine-based dimeric 3) acetylcholine esterase inhibitors, and many other divalent ligands. 1) We recently reported the first divalent neonicotinoid insecticides, alkylene-tethered bis-imidacloprid derivatives 4) and acyclic analogues.…”
Section: Introductionmentioning
confidence: 99%
“…
a b s t r a c tThe synthesis, molecular modeling, and pharmacological analysis of new multipotent simple, and readily available 2-aminopyridine-3,5-dicarbonitriles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and 2-chloropyridine-3,5-dicarbonitriles (21-28), prepared from 2-amino-6-chloropyridine-3,5-dicarbonitrile (1) and 2-amino-6-chloro-4-phenylpyridine-3,5-dicarbonitrile (2) is described. The biological evaluation showed that some of these molecules were modest inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), in the micromolar range.
…”
mentioning
confidence: 99%